Taxonomic revision and systematics of continental Australian pygmy water boatmen (Hemiptera: Heteroptera: Corixoidea: Micronectidae) - Tinerella, Paul P. (Zootaxa, 2013)
The pygmy water boatmen (Hemiptera: Heteroptera: Micronectidae) of continental Australiaare revised. The two genera and 17 species occurring in Australiaare fully described and keyed. The following species are transferred to Austronecta gen. nov.: Micronecta australiensis Chen, M. micra Kirklady, and M. carinata Chen. Austronecta bartzarum, sp. nov., is newly described. Within Micronecta Kirkaldy, thirteen species are recorded, including M. paragoga sp. nov. The following new synonymies are proposed: Micronecta illiesi Wróblewski, Micronecta concordia King and Micronecta dixonia King are junior synonyms of Micronecta annae Kirkaldy. A lectotype is designated for Micronecta tasmanica Wróblewski. Micronecta ludibunda Breddin is newly recorded for Australia, based on one male examined from Queensland. Within Australia, range extensions are recorded for the following species: Austronecta australiensis (New South Wales, Queensland); A. micra (Western Australia); Micronecta lansburyi Wróblewski (Western Australia); M. adelaidae Chen (Western Australia); M. major Chen (Queensland); M. halei Chen (South Australia); M. virgata Hale (Northern Territory); M. quadristrigata Breddin (Northern Territory); and M. queenslandica Chen (Northern Territory). All species are described and illustrated. Discussion and documentation of all primary type material is provided and where available, type specimens are illustrated. All male genitalic structures are illustrated with scanning electron micrographs. Line drawings are included for all other diagnostic characters, along with color habitus illustrations for both sexes of all species. Distribution maps are included for the following species: Austronecta micra, A. bartzarum, Micronecta paragoga, M. lansburyi, M. adelaidae, M. major, M. virgata, M. halei, M. quadrstrigata, and M. queenslandica. Diagnostic morphology and variation is discussed for all treated species. A phylogenetic analysis of Australasian micronectid generic relationships is presented. Discussion is provided on zoogeographic relationships of Australian Micronectidae.